Hubungan Dukungan Teman Sebaya Dengan Perilaku Kesehatan Reproduksi Pada Remaja Putri Di MTsN 42 Jakarta - Windi Setiyani (2021)
Teenage girls need peer support in going through puberty. Peers become one of the factors in determining the behavior of a teenager. A teenager will usually be easier to tell with their peers than with teachers or older people. This study aims to determine the relationship between peer support and reproductive health behavior in adolescent girls at MTsN 42 Jakarta. This research method uses cross sectional. The population in this study were young women at MTsN 42 Jakarta. The sampling technique used is random sampling with a sample of 146 respondents. Data analysis using the Chi Square test showed p-value = 0.002 (p-value <0.05), which means that there is a relationship between peer support and reproductive health behavior of adolescent girls at MTsN 42 Jakarta. Good peer support has an influence to shape good reproductive health behavior in adolescent girls. adolescent girls are expected to be able to choose their peers better and be able to use PIK-R in conducting consultations and counseling related to reproductive problems.